The Suppositional Ramsey Test and Decision-Instability. - Duca, Simone (Topoi: An International Review of Philosophy, 2011)
I analyse the relationship between the Ramsey Test (RT) for the acceptance of indicative conditionals and the so-called problem of decision-instability. In particular, I argue that the situations which allegedly bring about this problem are troublesome just in case the relevant conditionals are evaluated by non-suppositional versions, e.g. causal/evidential, of the test. In contrast, a suppositional RT, by highlighting the metacognitive nature of the evaluation of indicative conditionals, allows an agent to run a simulation of such evaluation, without yet committing her to the acceptance of such conditionals. I conclude that a suppositional interpretation of RT is superior to its non-suppositional counterparts and by briefly showing that a suppositional RT is compatible with a deliberational decision theory.